Stability and nonlinear dynamics in a Solow model with pollution - Ferrara, Massimiliano; Guerrini, Luca; Sodini, Mauro (Nonlinear Analysis: Modelling and Control, 2014)
In this paper, we introduce a time-to-build technology in a Solow model with pollution. We show that Hopf bifurcations occur as the delay passes through critical values. The direction and the stability criteria of the bifurcating periodic solutions are obtained by the normal form theory and the center manifold theorem. Numerical experiments confirm the analytical results with regard to the emergence of nonlinear dynamics.